"Who's Got Talent?" Change of Direction, Anthropometric Characteristics and Maturity Offset Differences Between Elite and Sub-Elite Young Soccer Player - Gatti, Alessandro; Azzali, Gianluca; Tornaghi, Michele; Lovecchio, Nicola; Giuriato, Matteo (Research quarterly for exercise and sport, 2025)
Agility, anthropometrics and maturity-offset have been considered fundamental for talent identification in soccer. The aim of this study is to compare 83 young soccer players (U12) from elite (28) and sub-elite (55) teams, to investigate the influences of anthropometric characteristics and maturation on Change-of-Direction (CoD) with the ball (dribbling) and without the ball. ANCOVA was run to investigate potential differences in Agility T-Test and Shuttle Dribble Test between categories while simultaneously controlling for the effects of anthropometric variables such as Peak Height Velocity (PHV), Weight, and Height. Agility T-Test performance does not significantly differ between the two categories (F-value = 0.537, p > .05). However, the Weight significantly influences the results (F-value = 18.425, p < .001, Eta-Squared = 0.172) and also PHV has a significant impact on them (F-value = 10.099, p < .01, Eta-Squared = 0.094). The Shuttle Dribble Test performance significantly varies between two groups (F-value = 5.207, p < .05, Eta-Squared = 0.057). Only Weight significantly influences this test (F-value = 4.324, p < .05, Eta-Squared = 0.048). Our findings indicate that during the U-12 age period, technical skills emerge as a crucial discriminant factor between elite and sub-elite young soccer players, contrarily to the athletic performance without the ball. In addition, the maturity stage specifically influences the Agility T-Test and Weight is significantly related to lower time to complete both in Agility T-Test and SDT.